Physical Activity Frequency of Special Olympic Athletes Ages 8-18 Across Economic Status - Rozak, Kathryn; Foley, Thomas John; MacDonald, Cathy; Bryan, Rebecca; Lloyd, Meghann; Temple, Viviene (European Journal of Adapted Physical Activity, 2017)
The purpose of the study was to examine self-reported physical activity frequency of an international sample of-children and youth aged 8-17 who participate in Special Olympics across economic status. A secondary aim was to-determine if there was a difference between males and females in physical activity frequency across economic status. Data from 12,243 children and youth were available from the Special Olympics International Healthy Athletes Database after data cleaning (7819 male and 4424 female). Prevalence rates were calculated with confidence intervals for physical activity occurring less than three days per week, or three or more days per week across economic status of country (low; lower middle; upper middle and high income status). A series of Chi-square tests were used to determine the differences in physical activity frequency across economic status and gender. Overall, 65.4% of-Special Olympics participants from low-income, 40.8% from lower-middle-income, 50.8% from upper-middle-income, and 61.6% from high-income economies reported 3 or more days of physical activity per week. Additionally, male Special Olympic athletes tended to be more physically active than their female counterparts. Further research is needed to understand reasons for these differences and determine how to increase overall physical activity.
Keywords: Health Disparity; Special Olympics Healthy Athletes; Intellectual Disability